The Influence of The Discovery Learning Learning Model Using Canva Media On Students Critical Thinking Abilities In Class XI History Learning At MAN - Suci, Sekar Wulan; Syarif Hadi Wibowo, Tubagus Umar; Maryuni, Yuni (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This research was conducted with the aim of finding out the effect of the discovery learning model using Canva media on students' critical thinking abilities in class XI history learning at MAN 1 Lebak. The research method used was a quasi experiment with a